Exploring social‐based discrimination among nursing home certified nursing assistants. Issue 1 (9th August 2019) - Travers, Jasmine L.; Teitelman, Anne M.; Jenkins, Kevin A.; Castle, Nicholas G.
Abstract: Certified nursing assistants (CNAs) provide the majority of direct care to nursing home residents in the United States and, therefore, are keys to ensuring optimal health outcomes for this frail older adult population. These diverse direct care workers, however, are often not recognized for their important contributions to older adult care and are subjected to poor working conditions. It is probable that social‐based discrimination lies at the core of poor treatment toward CNAs. This review uses perspectives from critical social theory to explore the phenomenon of social‐based discrimination toward CNAs that may originate from social order, power, and culture. Understanding manifestations of social‐based discrimination in nursing homes is critical to creating solutions for severe disparity problems among perceived lower‐class workers and subsequently improving resident care delivery.